PENGARUH PENERAPAN PEMBELAJARAN AKTIF TEKNIK PERMAINAN SUCKER BALL TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XI SOS SMA NEGERI 1 LEMBAH GUMANTI - Guswetri, Anifa (STKIP PGRI Sumbar, 2014)
Comprehension of mathematical concept of students that still low, cause studentthat still to consider mathematic of difficult student lessons and make bored. Sothat interest for study of student is insufficient. To overcome this problem soimplemented of learning process by applying sucker ball game. The purpose ofthis research is to see the whether by applying sucker ball game to have animpact to comprehension of mathematical concept of student in class XI SOSSMAN 1 Lembah Gumanti. This was an pre/experimental research which usedOne-shot case study research design. The population of research is the student inclass XI SOS SMAN 1 Lembah Gumanti. The selection of sample in this researchwhich used random toward the subject. Class XI SOS 2 that selected of sampleclass. The instrument used in this research is a quis and finish test the essay typeby reliability test =0,6125. So, it was concluded that the sucker ball game tohave impact for the students comprehension of mathematical concept.